Elimination of factors contributing to the development of colo-esophageal anastomotic dehiscence following retrosternal colonic esophagoplasty performed for esophageal atresia correction - A. N. Kivva; M. G. Chepurnoy; B. M. Belik; Yu. V. Tyshlek; M. Yu. Shtilman; A. A. Kivva; I. R. Chumburidze (Трансплантология (Москва))
Aim. Development of methodology that would allow surgeons to decrease the risk of colo-esophageal anastomotic dehiscence following esophagoplasty through prevention of colonic transplant compression in the retrosternal tunnel and surgery facilitation.Material and methods. Ultrasound examination was carried out on 43 infants (22 boys and 21 girls) without sternal pathologies. The dorsal sternal angle and thickness of the upper and lower parts of the sternal manubrium were evaluated. The prominence and structure of muscular arrangement in various parts of the dorsal side of the sternal manubrium were examined in 15 infant patients. The results of treatment based on the method developed in accordance with the RF invention patent No. 2552095 were analyzed for infant patients (8 boys and 7 girls) suffering from esophageal atresia. 9 patients had fenestration of the sternal manubrium performed across its entire length, 6 children – in its upper segment only. X-ray control was used to detect colonic transplant compression. Significant difference between the variables in question in the examined groups was evaluated using the Mann-Whitney U test (M-W) for data measured on an ordinal scale.Results. The upper part of the sternal manubrium (above the attachment of the first rib) was found to exert the highest pressure on the transplant as it is statistically significantly thicker (M-W=4.44; p<0.01), being covered with a more prominent muscular layer (M-W=6.71; p<0.001) over a larger area (M-W=4.42; p<0.01) and considerably reclined. In infant age, the dorsal sternal angle is 164.9±0.8 degrees. Its value was consistently (M-W=2.66; p<0.01) higher in the girls' group with significant individual variations. Based on the collected data, an original technique was developed for individual approach to the resection of the manubrium sterni applied during retrosternal colonic esophagoplasty in 15 patients with esophageal atresia. No signs of colo-esophageal anastomotic dehiscence or transplant compression were revealed in any of those cases.Conclusion. The suggested method allows surgeons to assess in every case the narrowness of retrosternal space and individually select the scope of sternal manubrium resection to eliminate important factors contributing to the development of colo-esophageal anastomotic dehiscence after retrosternal esophagoplasty in cases of esophageal atresia thus facilitating the surgery and preventing transplant compression in the retrosternal tunnel.